Immunohistochemical characterization of the expression of matrix metalloproteinase - 9 (MMP-9) and tissue inhibitor of matrix metalloproteinase (TIMP-1) in the invasive endometrioid endometrial carcinoma - A. V. Chepets (Zaporozhye State Medical University, 2015)
Endometrial carcinoma is the most common gynecological malignancy in developed countries. Aim. With the aim to determine MMP-9 and TIMP-1 expression levels in the invasive endometrioid endometrial carcinoma (EEC) cells and areas of the immunopositive cells in the center of the tumor and in the area of tumor invasion into the myometrium pathohistological, immunohistochemical and morphometric study of histological specimens of operative material of 56 women with pT1-4 stage of tumor was performed. Methods and results. It was found that MMP-9 and TIMP-1 expression occurs in 100% of invasive EEC. The ММР-9 expression level in the cytoplasm of tumor cells is high - 129.11±2.38 CUOD, which is 2,2 times more than its level in normal proliferative endometrium - 59.45±9.58 CUOD (p <0.05 ). The TIMP-1 expression level is 9.58±2.68 CUOD that is 2.69 times more than the expression level of TIMP-1 in normal proliferative endometrium (3.56±0.35 CUOD, p <0.05) . MMP-9 immunopositive cells make up 50.78±0.91% of area of invasive EEC tissue section and TIMP-1 immunopositive cells make up 3.76±0.15% of area of tumor tissue section. That is statistically significantly more than in normal proliferative endometrium, which has 23.31±1.31% of ММР-9 immunopositive cells and 2.82±0.14% of TIMP-1 immunopositive cells of endometrial glands. Differences between high levels of MMP-9 in the center of EEC and in the tumor myometrial invasion zone, as well as differences between the very low expression levels of TIMP-1 in these regions of the tumor were not statistically significant. With increasing of EEC histological grade the MMP-9 and TIMP-1 expression levels significantly increase (p <0.05). There is direct weak correlation between the MMP-9 and TIMP-1 expression levels in the cells of EEC (Pearson coefficient r =+0.31). Direct strong correlation between the expression level of MMP-9 in the tumor cells and the grade of tumor (Pearson coefficient r =+0.71) is revealed. Conclusion. The results of the study showed the increasing invasive capacity of EAE with the tumor grade increasing.